Perceived Safety in Community Parks: The Case of Erbil - Musheer, Siham K.; Abdullah, Hardi K.; abubakir, sidra salah (Journal of Linguistics and Social Sciences, 2024)
The parks are significant pillars of the city that fulfill various goals with clear objectives to engage. People can experience nature, engage in physical activity, and relax in parks. The research was based on a case study methodology to examine the reality of the park’s situation in residential neighborhoods through observations, in-person interviews, and a questionnaire. The study was conducted in neighborhoods and community parks within the city of Erbil (Sami Abdulrahman, Shanadar1, Peshmerga, Manar, Runaki, Kanyaw, Shanadar 2, Shanader 3, Gilkand, and Khanzad). The most significant conclusions from the study are: The research area's parks and gardens did not meet the requirements. In addition to lacking the majority of recreational amenities like sports fields and playgrounds, most parks offer areas for resting, strolling, and sitting down. According to the survey's findings, residents of Erbil's residential districts have a significant desire and curiosity to express their opinions in the city's parks. People of all ages, genders, and cultural backgrounds share this desire. Residents of the area make up the bulk of visitors to these parks and gardens (82%), and afternoons are the best times for them to visit., Additionally, only 8% of respondents think that these parks' playgrounds and exercise equipment satisfy their needs. Additionally, there is a great desire among visitors to add new recreational activities to these parks, such as sitting areas, family picnic areas, gathering areas for the elderly, play areas for kids, reading areas for school children, as well as walking corridors